(De-)personalization of mediated political communication: Comparative analysis of Yugoslavia, Croatia and the United Kingdom from 1945 to 2015. (October 2017) - Šimunjak, Maja
This article explores the ways in which the personalization of mediated political communication developed since 1945 in an authoritarian, transitional and established democratic system. Findings from a longitudinal content analysis of Yugoslav (authoritarian) and Croatian (transitional) daily newspapers are compared with those from Langer's study of personalization in the United Kingdom (established democracy). The comparison of the data related to the personalized media reporting from Yugoslavia and Croatia with that from the United Kingdom shows that the trends observed in the transitional context are counter to the existing personalization scholarship and that they run in the opposite direction from trends found in established democracies. Consequently, two new theories are formed that may help explain the personalization trends in transitional societies. These are continuation theory and democratization theory.